2015
DOI: 10.1111/eulj.12124
|View full text |Cite
|
Sign up to set email alerts
|

Should the EU Protect Democracy and the Rule of Law inside Member States?

Abstract: Against the background of recent developments in Hungary, the article discusses the question whether the European Union ought to play a role in protecting liberal democracy in Member States. First, it is argued that the EU has the authority to do so, both in a broad normative sense and in a narrower legal sense (though the latter is more likely to be disputed). The article then asks whether the EU has the capacity to establish a supranational militant democracy; here it is argued that at the moment both approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 3 publications
1
67
0
2
Order By: Relevance
“…(i) Compulsory exit: It has been suggested that the EU Treaties should be amended to give the EU the power to force a chronically non-compliant EU Member State out whereas the EU Treaties only currently foresee voluntary withdrawal from the Union; 65 (ii) The EU Charter of Fundamental Rights as a federal standard: According to this proposal defended by the former EU Justice Commissioner, Article 51(1) of the EU Charter of Fundamental Rights, which provides that its provisions only bind national authorities when they are implementing EU law, 66 should be repealed so as to make all EU fundamental rights 'directly applicable in the Member States, including the right to effective judicial review'; 67 (iii) Enabling EU jurisdiction via EU citizenship rights: First hinted at by Advocate General Poiares Maduro in Centro Europa, 68 this proposal essentially suggested to allow national courts, in a situation where fundamental rights of EU citizens would be systemically violated, to invite the Court of Justice to review the legality of national actions in the light of Article 2 TEU notwithstanding the fact that these violations may occur in wholly internal situations from a legal point of view, that is, outside the scope of application of EU law; 69 (iv) 'Outsourcing' of EU values' monitoring: The President of the Venice Commission has proposed to delegate the task of monitoring of EU countries' adherence to the rule of law to his organisation on the ground that it has a solid-track record when it comes to assessing and offering solutions to rule of law related problems in the 47 contracting parties to the Council of Europe; 70 (v) Creation of a new EU institution: Closely related to the previous proposal but in opposition to the idea of externalising any monitoring tasks and/or sanctioning powers, the setting up of a 'Copenhagen Commission' 71 has been suggested with the view of subjecting current EU Member States to a similar level of monitoring than EU candidates countries while removing this task from the European Commission as it would have failed in this endeavour;…”
Section: Positive Substantive Featuresmentioning
confidence: 99%
“…(i) Compulsory exit: It has been suggested that the EU Treaties should be amended to give the EU the power to force a chronically non-compliant EU Member State out whereas the EU Treaties only currently foresee voluntary withdrawal from the Union; 65 (ii) The EU Charter of Fundamental Rights as a federal standard: According to this proposal defended by the former EU Justice Commissioner, Article 51(1) of the EU Charter of Fundamental Rights, which provides that its provisions only bind national authorities when they are implementing EU law, 66 should be repealed so as to make all EU fundamental rights 'directly applicable in the Member States, including the right to effective judicial review'; 67 (iii) Enabling EU jurisdiction via EU citizenship rights: First hinted at by Advocate General Poiares Maduro in Centro Europa, 68 this proposal essentially suggested to allow national courts, in a situation where fundamental rights of EU citizens would be systemically violated, to invite the Court of Justice to review the legality of national actions in the light of Article 2 TEU notwithstanding the fact that these violations may occur in wholly internal situations from a legal point of view, that is, outside the scope of application of EU law; 69 (iv) 'Outsourcing' of EU values' monitoring: The President of the Venice Commission has proposed to delegate the task of monitoring of EU countries' adherence to the rule of law to his organisation on the ground that it has a solid-track record when it comes to assessing and offering solutions to rule of law related problems in the 47 contracting parties to the Council of Europe; 70 (v) Creation of a new EU institution: Closely related to the previous proposal but in opposition to the idea of externalising any monitoring tasks and/or sanctioning powers, the setting up of a 'Copenhagen Commission' 71 has been suggested with the view of subjecting current EU Member States to a similar level of monitoring than EU candidates countries while removing this task from the European Commission as it would have failed in this endeavour;…”
Section: Positive Substantive Featuresmentioning
confidence: 99%
“…The exposure of fundamental problems and pathologies of Europeanization reveals the pathological turn in European Studies (Börzel and Pamuk 2012;Mendelski 2014Mendelski , 2015. The awareness of the pathological effects of eu conditionality is particularly timely as several politicians as well as legal scholars argue that the eu has the legitimacy and potential tools to evaluate rule of law in membership countries (see Müller 2015;Closa and Kochenov 2016;Jakab and Kochenov 2016;Bogdandy and Sonnevend 2015). This argument seems premature given the eu's lingering rule of law evaluation deficit.…”
Section: Resultsmentioning
confidence: 99%
“…The EU, moreover, has been facing serious enforcement issues when Member States, such as Hungary and Poland, diverge from liberal democratic norms. 74 Thus, somewhat paradoxically, EU citizenship primarily structures relationships between EU citizenries rather than between individual EU citizens.…”
Section: European and National Democratic Relationshipsmentioning
confidence: 99%